Where $a_{1}=1$ and $a_{n+1}= \left ( n+1 \right )\left ( 1+a_{n} \right )$, $\forall \left ( n\epsilon \mathbb{N} \right )$

I have found that for this infinite product to be convergent, the series $\sum \ln \left ( 1+\frac{1}{a_{n}} \right)$ must also be convergent, and that if it has a finite sum, let's name it s, the value of the infinite product is $ e^{s}$. I am not sure whether $a_{n}=n\cdot \left ( 1+a_{n-1} \right )$ also holds true.

The given series passes the n-th term test, ok but how do I apply another test to it?

  • $\begingroup$ @Arian It's the first one, I was wondering if the second one could be derived from the first one. $\endgroup$ – Shemafied Nov 25 '14 at 20:31
  • $\begingroup$ If you divide by $(n+1)!$ your relation, you get $\displaystyle \frac{a_{n+1}}{(n+1)!}=\frac{a_n}{n!}+\frac{1}{n!}$. Hence you get $a_n=n!(\sum_{k=0}^{n-1}\frac{1}{k!})$. You have $a_n\sim e n!$, and this gives the convergence of the infinite product, but not its value. $\endgroup$ – Kelenner Nov 25 '14 at 20:49
  • $\begingroup$ @Shemafied: yes you can do that derivation. It stands for the same recurrence relation. $\endgroup$ – Arian Nov 25 '14 at 21:11

Note that $$a_{n+1}=(n+1)(1+a_n)\Rightarrow \frac{a_{n+1}}{1+a_{n}}=n+1$$ Consider the finite product:

$$\mathcal{P}_n=\prod_{n=1}^{N}(1+\frac{1}{a_n})=\prod_{n=1}^{N}\frac{1+a_n}{a_n}=\prod_{n=1}^{N}\frac{a_{n+1}}{(n+1)a_n}=\prod_{n=1}^{N}\frac{1}{(n+1)}\cdot \prod_{n=1}^{N}\frac{a_{n+1}}{a_n}=\frac{1}{N!}\cdot\frac{a_N}{a_1}=\frac{a_N}{N!}$$ Now we need to find an expression for the general term $a_n$. Notice that $$a_{n+1}=(n+1)(1+a_n)=(n+1)+(n+1)n(1+a_{n-1})=(n+1)+(n+1)n+(n+1)n(n-1)(1+a_{n-2})=...=(n+1)+(n+1)n+(n+1)n(n-1)+..+(n+1)n(n-1)(n-2)...2\cdot(1+1)$$ In other words $$a_{n+1}=\frac{(n+1)!}{n!}+\frac{(n+1)!}{(n-1)!}+..+2\cdot\frac{(n+1)!}{1!}$$ Hence $$a_N=\frac{N!}{(N-1)!}+\frac{N!}{(N-2)!}+..+2\cdot\frac{N!}{1!}$$ for all $N\geq1$ so $$\mathcal{P}_N=\frac{a_N}{N!}=\frac{1}{(N-1)!}+\frac{1}{(N-2)!}+..+\frac{2}{1!}$$ One can see that $$1\leq \mathcal{P}_N<\frac{1}{(N-1)(N-2)}+\frac{1}{(N-2)(N-3)}+..+2=3-\frac{1}{N-1}$$ then $$1\leq\lim_{N\to\infty}\mathcal{P}_N\leq3$$ Indeed the limit is $e$. Check it with the Taylor expansion of $e^x$ at $x=1$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.